Seeking Clarity in Murky Waters: Nuances of Equity and Social Justice From a Teacher Perspective - Chan, Elaine J. (Frontiers in Education, 2022)
In this study, I examined interactions between an English teacher and her students to illustrate ways in which issues of equity and social justice may play out in nuanced ways in the implementation of school curriculum in a diverse, Midwestern high school. These stories of classroom teacher and student experiences reveal complexities of how equity and social justice might unfold for students, and be understood by a teacher as she works with her students, to build a body of “teacher knowledge” (Clandinin and Connelly, 1996) that grows as the teacher gains experience. Examining complexities of “teacher knowledge” as a classroom teacher attempts to acknowledge her students’ social and cultural backgrounds while also implementing curriculum that meets requirements established by her school board, offers insight into challenges a teacher might encounter while working with students of diverse backgrounds in a school context.